Advancements in laboratory diagnostics for HIV/MTB coinfection: Integrating conventional methods with emerging technologies - Li, Yu; Wei, Hongjuan; Sun, Limei; Tang, Dongsong; Wang, Tiantian; Yu, Yanhua (Practical laboratory medicine, 2025)
Individuals infected with the Human Immunodeficiency Virus (HIV) face an elevated risk of Mycobacterium tuberculosis (MTB) infection. Clinical diagnosis of HIV/MTB coinfection presents substantial challenges, with co-infected patients exhibiting high mortality rates and representing a critical public health burden. The diagnostic process is complicated by atypical clinical presentations, frequent extrapulmonary tuberculosis involvement, difficulties in obtaining adequate sputum specimens, and low mycobacterial loads in samples—factors that severely limit the utility of conventional diagnostic methods such as sputum smear microscopy. Furthermore, HIV-associated immunosuppression diminishes the reliability of immunological diagnostic approaches. Recent advancements in molecular diagnostics have revolutionized tuberculosis detection in this vulnerable population. This review critically evaluates current laboratory methods for MTB detection in HIV/MTB co-infected individuals, analyzing their diagnostic performance, inherent limitations, and clinical applicability across diverse healthcare settings.